Motivation for academic work of student – future physical education teachers - Orce Mitevski; Biljana Popeska; Katerina Mitevska Petrusheva (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2020)
Personal approach toward learning process and interest for learning during university education are underlined as one of the key factors for success during university studies. The aim of this paper is to determine the motivation of students – future physical education teachers for academic work. The study was conducted on a sample of 69 participants, students in the first year at Faculty of physical education, sport and health at University in Skopje, North Macedonia. Questioner comprised from 11 items, designed as 4 – point Likert scale was applied. Three groups of indicators for academic work were determined: active involvement in teaching process; inner self – discipline for learning; strive to supplement and extend personal knowledge. Study results suggest on positive attitude toward academic work and respectively high level of motivation, different approaches in achieving results in academic work. Achieving long-lasting knowledge is underlined as a priority in the academic work of students included in this study. Obtained results are valuable for university professors indicating the key points that should be considered in order to achieve highly motivated students and maximal learning result.
Keywords: motivation, university students, learning, teaching process